(untitled) (Bulletin KNOB, 1994)
The present St John’s church partly dates back to after the fire of 1552. Not much is known about earlier predecessors of this church building. On the one hand, few written sources have been preserved and on the other hand, there has hardly been any research into this matter. At any rate, it is evident from the records that in 1404 a start was made with the new construction of a church which was consecrated in 1413. It concerned a three-aisled hall church with a blunt three-sided choir. In 1438 a large part of the church was burnt down, but in 1443 it could already be consecrated again. Concerning the period 1440-1489 there is a burial book on the basis of which (and with the aid of prosopographical research) the following conclusion can be drawn: after the fire of 1438 the three-aisled hall church was initially restored in its original form. It was only after 1475 that a start was made with the extension of this three-aisled church by means of new side aisles and a non-projecting transept. In view of the fact that simultaneously with this broadening, the old church was extended in eastward direction with the building of a choir with gallery, it is to be concluded that the broadening as well as the extension in eastward direction were part of one single building campaign.